Molecular Perspectives of Mitochondrial Adaptations and Their Role in Cardiac Proteostasis - Alam, Shafiul; Abdullah, Chowdhury S.; Aishwarya, Richa; Morshed, Mahboob; Bhuiyan, Md. Shenuarin (Frontiers in Physiology, 2020)
Mitochondria are the key to properly functioning energy generation in the metabolically demanding cardiomyocytes and thus essential to healthy heart contractility on a beat-to-beat basis. As the central organelle for cellular metabolism and signaling in the heart, dysfunction of the mitochondria leads to cardiovascular disease. The healthy mitochondrial functioning critical to maintaining cardiomyocyte viability and contractility is accomplished by adaptive changes in the dynamics, biogenesis, and degradation of the mitochondria to ensure cellular proteostasis. Recent compelling evidence suggests that the classical protein quality control system in cardiomyocytes is also under constant mitochondrial control, either directly or indirectly. Impairment of cytosolic protein quality control may affect the position of the mitochondria in relation to other organelles, as well as mitochondrial morphology and function, and could also activate mitochondrial proteostasis. Despite a growing interest in the mitochondrial quality control system, very little information is available about the molecular function of mitochondria in cardiac proteostasis. In this review, we bring together current understanding of the adaptations and role of the mitochondria in cardiac proteostasis and describe the adaptive/maladaptive changes observed in the mitochondrial network required to maintain proteomic integrity. We also highlight the key mitochondrial signaling pathways activated in response to proteotoxic stress as a cellular mechanism to protect the heart from proteotoxicity. A deeper understanding of the molecular mechanisms of mitochondrial adaptations and their role in cardiac proteostasis will help to develop future therapeutics to protect the heart from cardiovascular diseases.